Clinical Governance: Costs and Benefits - Kieran Walsh (Kerman University of Medical Sciences, 2014)
Dear Editor, Ravaghi et al. should be congratulated for offering a fascinating insight into the views of senior managers on the implementation of clinical governance (1). Clearly many had experience of challenges in implementation and there were different types of challenges. However, a common theme ran through many of the challenges, and that theme is one of cost. The managers did not mention cost explicitly but the issue was clearly implicit. They spoke of the need for more resources, support and staff engagement-all of which are associated with costs. We would do well to ask outright: what are the costs of implementing clinical governance? Such costs are likely to be significant, and are likely to be made up of all the components of clinical governance including, as the authors outline, "clinical effectiveness, clinical audit, risk management, patient and public involvement, education and training, staff management, and use of information" (2).